Labor Due Diligence: An essential tool in mergers and acquisitions - Tsuboyama Shiohama, Liliana (2014)
Presently, labor audit, also known as labor due diligence, is a very important tool used in theprocess of merges and acquisitions. According to the results obtained, negotiations on the final price of the merge or acquisition will depend on it.In the present article, the author explains the procedure, emphasizing the importance that its correct application might have in any merger or acquisition process, being adetermining factor for the process’ success.